La guerra civil de 1859 y los límites de la modernización en Atacama y Coquimbo - Ortega Martínez, Luis; Rubio Apiolaza, Pablo (Revista de Historia Social y de las Mentalidades, 2025)
The 1895 civil war was one of the first conflicts t hat the Chilean republican society had to face. This incident had an enormous impact in the regions of the “small north”. If the four months that the conflict lasted are analyzed, it is possible to find some indicators that suggest the existence of a “local bourgeois”, and a lso traces of a growing autonomy that defied the foundations of the Chilean state. This e ssay reviews, with an interpretative character, the social and economic context of mid n ineteenth century. It also analyzes the conflict itself, establishing that its development can not be understood separately from the tension between modernization and tradition that th e mining provinces of Atacama andCoquimbo faced. From an institutional point of view, the civil war gave birth to a period in which political agreements prevailed over open conf rontations.